Deep-blue high-efficiency triplet-triplet annihilation organic light-emitting diodes using donor- and acceptor-modified anthracene fluorescent emitters. (September 2021) - Cao, C.; Yang, G.-X.; Tan, J.-H.; Shen, D.; Chen, W.-C.; Chen, J.-X.; Liang, J.-L.; Zhu, Z.-L.; Liu, S.-H.; Tong, Q.-X.; Lee, C.-S.
Abstract: Deep-blue organic electroluminescence (EL) emitters are important for full-color display and solid-state lighting applications of organic light-emitting diode (OLED) technology. Triplet-triplet annihilation (TTA) is one efficient approach for realizing efficient deep-blue EL. In this study, a PPI donor and a BI acceptor are connected via an anthracene (AN) bridge to obtain a bipolar deep-blue TTA emitter, PPI-AN-BI . The effects of the donor and the acceptor moieties are studied by comparing photophysical properties of molecules obtained by replacing either the PPI or the BI group with a phenyl (P) group to obtain BI-AN-P or PPI-AN-P . Non-doped OLEDs based on the three molecules display high-performance deep-blue EL. Using PPI-AN-BI as a non-doped emitter, a trilayer device exhibits a maximum external quantum efficiency (EQE) of 8.4% with a CIE index of (0.15, 0.15), and a bilayer device exhibits a maximum EQE of 6.9% with a CIE index of (0.15, 0.15). It is experimentally and theoretically demonstrated that triplet pair transition and enhanced oscillator strength can be the main reasons contributing to high performances. This work would provide an efficient method for designing deep-blue non-doped EL emitters. Graphical abstract: Image 1 Highlights: Three triplet-triplet annihilation emitters with rigid structures achieve high photoluminescent quantum yield. Highly efficient nondoped trilayer and bilayer blue OLEDs achieve external quantum efficiency up to 8.4% and 6.9%, respectively. The systemic stucture-properties of anthancene derivatives were fully explored.